The AI Co-pilot: Navigating Market Turbulence and Charting a Course for Sustainable Advantage - Simon Suwanzy Dzreke (International Journal of Management Science and Application, 2025)
This study addresses the gap in frameworks for effective human-AI collaboration in strategic decision-making during turbulent market conditions. Using a mixed-methods approach (longitudinal case studies in manufacturing, finance, and logistics; large-scale executive surveys; computational simulations), we empirically evaluate the "AI co-pilot" model, where AI augments human strategic cognition. Results show AI co-pilots improve market disruption prediction accuracy by 30-50% and reduce strategic response latency. However, these benefits critically depend on governance frameworks ensuring algorithmic accountability, dynamic trust calibration, and human agency preservation. Case studies (e.g., AI-enabled semiconductor shortage detection enabling proactive diversification) demonstrate value, while instances of algorithmic opacity highlight the necessity of human oversight. Maintaining competitive advantage requires interfaces ("algorithmic diplomacy"), balancing AI's computational power with human judgment, wisdom, and ethics. Organizations achieving this symbiosis gain superior resilience, transforming volatility into adaptive innovation opportunities.